Engineering and Purification of Microcin C7 Variants Resistant to Trypsin and Analysis of Their Biological Activity - Guangxin Yang; Lijun Shang; Lu Liu; Zeqiang Li; Xiangfang Zeng; Xiuliang Ding; Jinxiu Huang; Shiyan Qiao; Haitao Yu (MDPI AG, 2023)
Microcin C7 (McC) as a viable form of antimicrobial has gained substantial attention due to its distinctive antimicrobial activity, by targeting aspartyl tRNA synthetase. McC can be a potential solution against pathogenic microbial infections in the postantibiotic era. However, considering that degradation by digestive enzymes can disrupt the function of this peptide in the gastrointestinal tract, in this study, we attempt to design McC variants to overcome several barriers that may affect its stability and biological activity. The mccA gene encoding the McC peptide precursor was mutated and 12 new McC variants with trypsin resistance were found. The Yej+rimL− strain was used as an indicator to determine the minimum inhibitory concentrations (MICs). The results showed that three variants, including R2A, R2T and R2Q, among 12 variants formed by the replacement of the second arginine of the McC peptide with different amino acids, were resistant to trypsin and had an outstanding antimicrobial ability, with MIC values of 12.5, 25, and 25 μg/mL, respectively. Taken together, our findings show that the engineering of the site-directed mutagenesis of McC significantly enhances McC trypsin resistance and maintains a great antimicrobial activity.